Changes in physical properties of extruded sour cassava starch and quinoa flour blend snacks - Taverna,Lívia Giolo (2012)
Given the broad acceptance of sour cassava starch biscuits in Brazil and the nutritional quality of quinoa flour, this study aimed to evaluate the effect of extrusion temperature, screw speed, moisture, and amount of quinoa flour on the physical properties of puffed snacks. Extrusion process was carried out using a single-screw extruder in a factorial central composite design with four factors. Effects of moisture and amount of quinoa flour on the expansion index and specific volume of snacks were observed. There was a pronounced increase in water solubility index of blends with the extrusion process with significant effects of all process parameters on the WSI. Higher water absorption index (WAI) was observed under high temperature, low moisture, and lower quinoa flour amount. Temperature and amount of quinoa flour influenced the color of the snacks. A positive quadratic effect of quinoa flour on hardness of products was observed. Blends of sour cassava starch and quinoa flour have good potential for use as raw material in production of extruded snacks with good physical properties.